Architectural overview of the SPEAKeasy system. - Cook, P.G (IEEE Journal on selected areas in communications)
SPEAKeasy is a successful implementation of a software-defined radio (SDR) for military applications. It permits general-purpose digital hardware to communicate over a wide range of frequencies, modulation techniques, data encoding methods, cryptographic types, and other communication parameters. The background of SDRs for military and commercial needs is discussed, and the SPEAKeasy architecture is defined